2022
DOI: 10.1021/acsomega.2c01755
|View full text |Cite
|
Sign up to set email alerts
|

Microstructural Modeling and Simulation of a Carbon Black-Based Conductive Polymer─A Template for the Virtual Design of a Composite Material

Abstract: Carbon black is the most frequently applied conductive additive in rubber and polymer composites. In this work, we show how a carbon black microstructure in a polymer matrix can be conclusively modeled based on carbon black aggregation as well as an agglomeration mechanism using a state-of-the-art mathematical model. This novel and flexible microstructural modeling method enables us to virtually investigate the morphology of conductive additives within a polymer matrix and can be adapted to many conductive pol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 40 publications
0
7
0
Order By: Relevance
“…The carbon particles used for unstable CB dispersion have a smaller particle size than the CB species in the stable dispersion as can be seen in Figure 7. This should work in favor of the smaller particle size 61–65 . The opposite trend is found.…”
Section: Resultsmentioning
confidence: 89%
See 3 more Smart Citations
“…The carbon particles used for unstable CB dispersion have a smaller particle size than the CB species in the stable dispersion as can be seen in Figure 7. This should work in favor of the smaller particle size 61–65 . The opposite trend is found.…”
Section: Resultsmentioning
confidence: 89%
“…They observed that smaller particles ( D = 40 nm vs. D = 250 nm) lead to better electrical conductivity at a similar volume fraction. For different aggregation sizes (19–90 nm particles) they did not find a trend due to positive and negative effects canceling each other out 65 . Intuitively one might think that a better distribution of particles should generally lead to a better electrical conductivity.…”
Section: Resultsmentioning
confidence: 89%
See 2 more Smart Citations
“…Figure g demonstrates the CNF/TPU obtained after anchoring the carbon nanofibers, that a large number of chopped CNFs are vertically anchored to the surface of the substrate fibers along the direction of solvent-induced force, and a stable high-density nanobrush structure is constructed based on the compatibility dispersion force between the two weakly polar materials, the mechanically interlocking structure generated by the swelling of the surface of the substrate fibers and combined with the directional repulsive effect of the strongly polar solvent environment, while a small number of CNFs are spanned across several fibers to form a sliding connecting bridge. Continued loading of CB in the form of grape cluster-like agglomerates tightly layered to fill the voids in the network structure of CNF to form a three-dimensional nanobrush-bridging structure, which drastically increases the density of conductive paths (Figure h) . The large loading of carbon nanomaterials resulted in more than 2-fold increase in the diameter of the composite fibers, demonstrating the effectiveness of the polarity-induced effect and the feasibility of employing mixed carbon fillers to construct an active functional layer.…”
Section: Resultsmentioning
confidence: 97%